2018
DOI: 10.1098/rstb.2016.0446
|View full text |Cite
|
Sign up to set email alerts
|

Somatic growth and telomere dynamics in vertebrates: relationships, mechanisms and consequences

Abstract: Much telomere loss takes place during the period of most rapid growth when cell proliferation and potentially energy expenditure are high. Fast growth is linked to reduced longevity. Therefore, the effects of somatic cell proliferation on telomere loss and cell senescence might play a significant role in driving the growth-lifespan trade-off. While different species will have evolved a growth strategy that maximizes lifetime fitness, environmental conditions encountered during periods of growth will influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
287
3
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(328 citation statements)
references
References 128 publications
(159 reference statements)
16
287
3
1
Order By: Relevance
“…Such trade‐offs may account for the plethora of findings that suggest adverse early‐life conditions negatively affect lifespan and lifetime reproductive success (LRS; Kruuk, Clutton‐Brock, Rose, & Guinness, ; Lindström, ; Nussey, Kruuk, Morris, & Clutton‐Brock, ; Tung, Archie, Altmann, & Alberts, ), which can occur when animals invest in growth or competitiveness during development at the expense of their later‐life fitness (Vedder, Verhulst, Bauch, & Bouwhuis, ). The mechanisms behind such patterns are unclear, but recently it has been suggested that telomeres, the nucleoprotein structures at the terminal end of chromosomes, could link early‐life conditions and developmental growth to lifespan and ultimately LRS (Monaghan & Haussmann, ; Monaghan & Ozanne, ).…”
Section: Introductionmentioning
confidence: 99%
“…Such trade‐offs may account for the plethora of findings that suggest adverse early‐life conditions negatively affect lifespan and lifetime reproductive success (LRS; Kruuk, Clutton‐Brock, Rose, & Guinness, ; Lindström, ; Nussey, Kruuk, Morris, & Clutton‐Brock, ; Tung, Archie, Altmann, & Alberts, ), which can occur when animals invest in growth or competitiveness during development at the expense of their later‐life fitness (Vedder, Verhulst, Bauch, & Bouwhuis, ). The mechanisms behind such patterns are unclear, but recently it has been suggested that telomeres, the nucleoprotein structures at the terminal end of chromosomes, could link early‐life conditions and developmental growth to lifespan and ultimately LRS (Monaghan & Haussmann, ; Monaghan & Ozanne, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, individuals can compensate poor developmental performance during early life by accelerating growth rate to catch up later when environmental conditions are more favourable, especially in animals that exhibit lifelong somatic growth, such as fish. Mechanisms for the deleterious effects of catch-up growth are often poorly understood but might include elevated levels of oxidative stress (Metcalfe & Alonso-Alvarez, 2010;Monaghan & Ozanne, 2018;Monaghan et al, 2009). Mechanisms for the deleterious effects of catch-up growth are often poorly understood but might include elevated levels of oxidative stress (Metcalfe & Alonso-Alvarez, 2010;Monaghan & Ozanne, 2018;Monaghan et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, markers of stress experienced during the life course may accumulate in the telomeres (Herborn et al, 2014;Monaghan, 2014). Each cycle of cell division shortens the noncoding repetitive sequences of the telomeres, and fast somatic growth can accelerate this process (Monaghan & Haussmann, 2006;Monaghan & Ozanne, 2018). Each cycle of cell division shortens the noncoding repetitive sequences of the telomeres, and fast somatic growth can accelerate this process (Monaghan & Haussmann, 2006;Monaghan & Ozanne, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in tropical species, reproductive workload is reduced as they lay smaller clutches, thereby caring for fewer young and expending less energy than temperate birds (Nilsson, 2002;Tieleman et al, 2006). These slower growth trajectories in combination with increased parental care per offspring may favor lower levels of telomere attrition during early life in tropical birds, which in turn may be important determinants of their longer life spans (Monaghan & Ozanne, 2018). In addition, tropical songbirds seem to have lower post-natal metabolic rates and slower, more sustained growth despite similar nestling times than temperate birds (Martin, 2015;Ton & Martin, 2016).…”
Section: Both Longitudinal and Cross-sectional Studies In Birds Showmentioning
confidence: 99%